2023
DOI: 10.25122/jml-2021-0436
|View full text |Cite
|
Sign up to set email alerts
|

The effect of movement therapy with progressive muscle relaxation on the depression rate of patients admitted to the psychiatric ward of Moradi Rafsanjan Educational and Medical Center in 2021

Abstract: Depression is the most prevalent psychiatric disorder and has received more attention due to its adverse outcomes, including suicide and a severe decrease in social and individual functioning. To this end, the present study examined the effect of movement therapy and progressive muscle relaxation on the depression rate in depressed patients. In the present interventional study, 60 patients diagnosed with major depression and hospitalized at Moradi Hospital's psychiatric ward in Rafsanjan in 2020, with an age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The study is also fully supported by the results of outside research conducted by [14], which also showed a significant difference (P < 0.001) in the average stress and depression scores before the intervention (37.26±7.70) and after the intervention (8.01±5.22) in the intervention group. This finding confirmed the positive effect of progressive muscle relaxation therapy in reducing stress and depression in the elderly.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The study is also fully supported by the results of outside research conducted by [14], which also showed a significant difference (P < 0.001) in the average stress and depression scores before the intervention (37.26±7.70) and after the intervention (8.01±5.22) in the intervention group. This finding confirmed the positive effect of progressive muscle relaxation therapy in reducing stress and depression in the elderly.…”
Section: Resultssupporting
confidence: 77%
“…Four answer options are provided for each statement: 0: Does not suit me at all, or never: 1) Corresponds with me to some degree or sometimes; 2) Corresponds with me to a degree that can be considered, or quite often; 3) It suits me very much, or very often. In addition, this questionnaire also has five levels of stress categories, namely stand-ard (0-7), mild (8)(9), moderate (10)(11)(12), severe (13)(14)(15)(16) and very severe (17+) stress.…”
Section: Methodsmentioning
confidence: 99%